Bioprospecção de leveduras fermentadoras de xilose visando a produção de etanol a partir de bagaço de cana-de-açúcar - Silva, Rosimeire Oenning da [UNESP] (2015)
The biomass lignocellulosic is an source alternative for the production of etha-nol. Among the substrates produced in Brazil sugar cane bagasse is abundant and available. Compatible with the generation of bagasse use would be the production ethanol. Two ways are possible hydrolysis of bagasse, the chemical and enzymatic. Whatever the route of the hydrolysis the must contain D-xylose to be the most abun-dant pentose in the constitution of the lignocellulosic material. The availability of mi-cro-organisms that ferment pentose sugars is essential for the development of pro-cesses for production of hemicellulosic ethanol. To overcome this limitation the re-search sought to select strains of yeast capable of converting xylose present in the semisynthetic medium and hemicellulose in bagasse hydrolyzate of cane sugar into ethanol. To both samples was performed on samples of flowers and cane juice and isolation of the strains was done in medium containing xylose as a carbon source. There was screened by means of biological tests for the evaluation of ethanol pro-duction following the methodology for screening plates. The yeasts that showed posi-tive responses in the test plates were identified through sequencing of D1 / D2 do-mains of the rDNA. A total of one hundred sixty-five isolates, four were selected for their possible ability to ferment D-xylose. These Yeast were idenfified as Wicker-hamomyces anomalus, Schizosaccharomyces pombe and Starmerella meliponino-rum. Quantitative evaluation of ethanol production from xylose were made and for comparison were also evaluated ethanol production from glucose. The yeast that produced ethanol in semisynthetic medium were selected for fermentation of hemi-cellulose hydrolyzate bagasse cane sugar. For this evaluation sugarcane bagasse was subjected to acidic hydrolysis and concentrated detoxified with active charcoal. Cell growth and viability by counting in a Neubauer chamber, glucose, xylose, xylitol ...